The Effect of Human Rights and Organizational Virtue Levels in Sports on Personnel Empowerment - Nuri Berk Güngör; Serkan İbiş; Alptuğ Soyer (Research in Sport Education and Sciences)
This study aimed to determine the relationship between human rights in sports and organisational virtuousness levels of academicians working in the field of sports sciences and staff empowerment. The study group of the research consisted of a total of 335 participants (63 females and 272 males) working in various universities of Turkey. To determine the current situation, the model of the research is a relational survey method. In this study, Human Rights Attitude Scale in Sport (HRASS) developed by Sadık (2014), Organisational Virtuousness Scale (OVS) developed by Cameron et al., (2004) and adapted into Turkish by Erkmen and Esen (2012), and Employee Empowerment Scale (EES) developed by Spreitzer (1995) and adapted into Turkish by Sürvegil et al., were used as data collection tools. In the analysis of the data, T-Test, Post Hoc Test, One-way ANOVA, Pearson Correlation and Linear Regression Analysis methods were used in addition to descriptive statistics on data with thinned normality distribution. As a result of the analysis, it was determined that the participants' Human Rights Attitudes in Sports, Organizational Virtue, and Employee Empowerment levels were above the average scores. Considering the average scores of the participants, it can be stated that the results are supported by the literature. In addition to a low positive significant relationship between HRASS and OVS, a moderate positive relationship was found between HRASS and EES. Additionally, a low-level positive relationship was detected between the participants' OVS and EES. A statistically significant relationship was detected between HRASS, OVS and EES, and it was determined that human rights and organizational virtue in sports had a 15% explanation power of employee empowerment. As a result, it can be stated that academicians' human rights in sports and organizational virtuousness levels positively affect employee empowerment.